2017
DOI: 10.1177/000313481708300524
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Trauma in the Oldest of the Old: An Analysis of the Nationwide Inpatient Sample

Abstract: Thoracic trauma (TT) has the second highest mortality rate in the geriatric population. These injuries cause significant morbidity in elderly patients. Little has been done to describe the demographics and mortality of specific injuries in these patients. ICD-9 codes corresponding with thoracic trauma for patients aged >80 years were extracted from the Nationwide Inpatient Sample database from 2000 to 2010. Characteristics including gender, race, Charlson Comorbidity Index (CCI), length of stay (LOS), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The risk of all health care utilization outcomes increased in this cohort of patients with each additional year of age. This supports previous research, which has reported age to be a predictor of poor hospital-based resource outcomes in patients with blunt chest wall trauma, including delayed upgrade in care, need for critical care admission, and mechanical ventilation and prolonged length of stays 28–32 . Minor blunt chest wall injuries that are typically well tolerated by younger patients can often prove fatal for the older patient, which would explain the increase in healthcare resource utilization with each year of age, reported in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The risk of all health care utilization outcomes increased in this cohort of patients with each additional year of age. This supports previous research, which has reported age to be a predictor of poor hospital-based resource outcomes in patients with blunt chest wall trauma, including delayed upgrade in care, need for critical care admission, and mechanical ventilation and prolonged length of stays 28–32 . Minor blunt chest wall injuries that are typically well tolerated by younger patients can often prove fatal for the older patient, which would explain the increase in healthcare resource utilization with each year of age, reported in this study.…”
Section: Discussionsupporting
confidence: 91%
“…This supports previous research, which has reported age to be a predictor of poor hospital-based resource outcomes in patients with blunt chest wall trauma, including delayed upgrade in care, need for critical care admission, and mechanical ventilation and prolonged length of stays. [28][29][30][31][32] Minor blunt chest wall injuries that are typically well tolerated by younger patients can often prove fatal for the older patient, which would explain the increase in healthcare resource utilization with each year of age, reported in this study. With an aging demographic, trauma in the older patient will continue to increase most likely with a high volume of rib fractures.…”
Section: Discussionmentioning
confidence: 76%
“…Congestive heart failure was a significant risk factor in six studies 2 17 33 53 56 72. Pre-existing conditions were also reported to be a risk factor as measured by the Elixhauser Comorbidity Count,5 and Charlson Comorbidity Score 14 78. One study reported comorbidities as a significant risk factor for death, but without defining comorbidities 35…”
Section: Resultsmentioning
confidence: 99%